Selection and Incentives under Time Pressure: The Importance of Framing - Maria De Paola; Francesca Gioia; Valeria Pupo (Institute of Labor Economics (IZA), 2020)
In this paper we investigate whether the framing of the incentives used to foster participation into contexts characterized by high degrees of time pressure affects individuals' self-selection. At this aim we run a lab-in-the-field experiment structured in two parts. The first part investigates individual characteristics that affect performance under time pressure, while the second is devoted to analyze how the decision to work under time pressure is affected by the reward/punishment framing of incentives. We find that individuals characterized by a high degree of risk aversion perform worse under time pressure. Nonetheless, when facing a penalty incentive scheme these individuals are more likely to choose to work with strict term limits, suggesting that penalty contracts might generate adverse selection problems.
Keywords: C9; C91; D01; D91; J33; 330; time pressure; bonus; penalty; incentive schemes; framing; selection; lab-in-the-field experiment